Thermo-behavioural responses to orally applied l-menthol exhibit sex-specific differences during exercise in a hot environment - Parton, A. J.; Waldron, M.; Clifford, T.; Jeffries, O. (Physiology & Behavior, 2021)
Aims: This study investigated the efficacy of l-menthol mouth-rinsing on thermal sensation and perceived effort in females and males, using a fixed-rating of perceived exertion (RPE) exercise protocol in a hot environment. Methods: Twenty-two participants (eleven females, eleven males) completed two trials using a fixed-RPE protocol at an exercise intensity between `hard` and `very hard`, equating to 16 on the RPE scale at ~35 °C. Participants adjusted power output to maintain RPE-16. In a randomised, double-blind, crossover design, l-menthol or a control mouthwash was administered at an orally neutral temperature (~32 °C) prior to exercise and at 10 min intervals thereafter. Measures of mechanical power output, core temperature, heart rate, perception of thermal sensation and thermal comfort, and whole-body sweat loss are reported. Results: Thermal sensation was lowered by l-menthol in both sexes (P < 0.05), however during exercise this was only maintained for 40% of the trial duration in females. Thermal comfort did not differ between conditions (P > 0.05). No differences in exercise duration were observed compared to control, despite a ~4% and ~6% increase in male and females respectively. Power output increased by ~6.5% males (P = 0.039) with no difference in females ~2.2% (P = 0.475), compared to control. Core temperature, heart rate and whole-body sweat loss was not different between condition or sex. Conclusions: l-menthol lowered perceptual measures of thermal sensation in females, but did not attenuate a greater rate of rise in thermal sensitivity when exercising in a hot environment, compared to males. Males appeared to adopt a higher risk strategy by increasing power output following l-menthol administration in contrast to a more conservative pacing strategy in females. Therefore, there appear to be sex-specific differences in l-menthol's non-thermal cooling properties and subsequent effects on thermo-behavioural adjustments in work-load when exercising in a hot environment.